Simulations For Steam Methane Reforming Over Ni/Al2O3 Catalyst In A Fixed Bed Reactor And A Membrane Reactor - Chan, Kit Yen (Universiti Sains Malaysia, 2021)
The limitations of steam methane reforming (SMR) process in fixed bed reactor (FBR) is thermodynamic equilibrium constraint and the requirement of high operating temperature. Membrane reactor (MR) have huge application potential for the equilibrium limited, endothermic SMR process due to the simultaneous withdrawal of reaction product, H2. The steady-state behavior of SMR process in FBR and MR are examined by developing a 1-D, pseudo-homogeneous mathematical modelling framework that operates at isothermal and isobaric mode. The calculation procedures was performed using MATLAB and both of the reactor models were validated against experimental data. Comparative SMR performance assessment in terms of methane conversion (XCH4), H2 yield and selectivity of CO (SCO) and CO2 (SCO2) between FBR and MR were accordingly conducted. The increasing temperature has positive impact on XCH4 and H2 yield, but at temperature above 650 ℃, the positive impact of H2 removal in MR becomes less significant compared to FBR. Besides, SCO2 and SCO are only affected by temperature in which increasing temperature promotes the reverse water gas shift reaction, resulting in the increase of SCO. For FBR, SCO exceeds SCO2 at around 590 ℃ while for MR, SCO exceeds SCO2 at around 610 ℃. Next, the effect of increasing reaction pressure show an opposite trend for MR and FBR, in MR, higher XCH4 is obtained when pressure increases due to the increase of H2 partial pressure driving force but in FBR, higher pressure is not favoured. In addition, methane inlet flow rate higher than 0.03 kmol/h suppressed the positive impact of H2 removal in MR while lower permeation zone pressure (Pperm) and higher sweep gas flow rate improve the reaction performance in MR.